The Behavioral Economics of Crime and Punishment - Ali al-Nowaihi
The Becker proposition (BP) is one of the founding pillars of the modern literature on Law and Economics. It states that it is optimal to impose the severest possible punishment (to maintain effective deterrence) at the lowest possible probability (to economize on enforcement costs). The BP is not consistent with the evidence. This is known as the Becker paradox. Using evidence from a wide range of phenomena we show that none of the proposed explanations for the Becker paradox are satisfactory. The BP has largely been considered within an expected utility framework. We clarify the Becker proposition and its welfare implications under expected utility. We show that BP also holds under rank dependent expected utility and cumulative prospect theory, the two main alternatives to expected utility. al-Nowaihi and Dhami (2010a) recently propose composite cumulative prospect theory that combines prospect theory with cumulative prospect theory. Under plausible conditions CCP is able to resolve the Becker paradox. Our article opens the way for incorporating non-expected utility theories into an economic analysis of criminal activity.Behavioral economics; Illegal activity; Expected utility theory; Rank dependent expected utility; Prospect theory; Prelec and composite Prelec probability weighting functions; Composite cumulative prospect theory; Punishment functions